Genetic Manipulation of Sirtuin 3 Causes Alterations of Key Metabolic Regulators in Melanoma - Singh, Chandra K.; George, Jasmine; Chhabra, Gagan; Nihal, Minakshi; Chang, Hao; Ahmad, Nihal (Frontiers in Oncology, 2021)
The mitochondrial sirtuin SIRT3 plays key roles in cellular metabolism and energy production, which makes it an obvious target for the management of cancer, including melanoma. Previously, we have demonstrated that SIRT3 was constitutively upregulated in human melanoma and its inhibition resulted in anti-proliferative effects in vitro in human melanoma cells and in vivo in human melanoma xenografts. In this study, we expanded our data employing knockdown and overexpression strategies in cell culture and mouse xenografts to further validate and establish the pro-proliferative function of SIRT3 in melanocytic cells, and its associated potential mechanisms, especially focusing on the metabolic regulation. We found that short-hairpin RNA (shRNA) mediated SIRT3 knockdown in G361 melanoma cells showed diminished tumorigenesis in immunodeficient Nu/Nu mice. Conversely, SIRT3 overexpressing Hs294T melanoma cells showed increased tumor growth. These effects were consistent with changes in markers of proliferation (PCNA), survival (Survivin) and angiogenesis (VEGF) in xenografted tissues. Further, in in vitro culture system, we determined the effect of SIRT3 knockdown on glucose metabolism in SK-MEL-2 cells, using a PCR array. SIRT3 knockdown caused alterations in a total of 37 genes involved in the regulation and enzymatic pathways of glucose (32 genes) and glycogen (5 genes) metabolism. Functions annotation of these identified genes, using the ingenuity pathway analysis (IPA), predicted cumulative actions of decreased cell viability/proliferation, tumor growth and reactive oxygen species (ROS), and increased apoptosis in response to SIRT3 knockdown. Further, IPA gene network analysis of SIRT3 modulated genes revealed the interactions among these genes in addition to several melanoma-associated genes. Sirtuin pathway was identified as one of the top canonical pathways showing the interaction of SIRT3 with metabolic regulatory genes along with other sirtuins. IPA analysis also predicted the inhibition of HIF1α, PKM, KDM8, PPARGC1A, mTOR, and activation of P53 and CLPP; the genes involved in cancer development and progression. Collectively, these results suggest that SIRT3 inhibition affects cellular metabolism, to impart an anti-proliferative response against melanoma.